BLACK FEMINISM IN SELECTED POEMS BY AUDRE LORDE AND LUCILLE CLIFTON - Widyaswara, Ni Made (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
ABSTRACTThis research aims to find the struggles of black women against oppression and beauty standards that appear in the poetry of Audre Lorde and Lucille Clifton. In this study, the researcher analyzed two poems from each of the two poets in a way; the first is how black women fight oppression and beauty standards by examining the ideas and history of black feminists in the US in order to obtain extrinsic elements of poetry. And the second, analyzing the intrinsic elements in the poetry to find the figurative language and imagery used in these poems. Data were analyzed by the resistance theory of black women by Patricia Hills Collins. Another theory is figurative language and imagery by Ruth Miller and Robert A. Greenberg. The data is produced from words, phrases and sentences that relation to the black feminism as the struggle of black women resist oppression and standard beauty that contain in the poems. The first way to resistance is Self-Definition, Self-Respect, Self-Independence, and Personal Empowerment mentioned by Collins. Then, in the poems uses figurative language such as metaphor, simile and personification. Imagery also includes visual, tactile and aural. Finally, the conclusion that can be drawn is that the findings above prove that the poetry of Audre Lorde and Lucille Clifton is the struggle of black women against injustice.Key words: Black Women, Black Feminism, Controlling Images, Positive Self-Esteem, Poetry. ABSTRAKPenelitian ini bertujuan untuk menemukan perjuangan perempuan kulit hitam melawan penindasan dan standar kecantikan yang muncul dalam puisi Audre Lorde dan Lucille Clifton. Dalam penelitian ini, peneliti menganalisis dua puisi dari masing-masing dua penyair tersebut dengan cara; Pertama, bagaimana perempuan kulit hitam melawan penindasan dan standar kecantikan dengan mengkaji gagasan dan sejarah feminis kulit hitam di AS untuk mendapatkan unsur ekstrinsik puisi. Dan yang kedua, menganalisis elemen intrinsik dalam puisi untuk menemukan bahasa kiasan dan perumpamaan yang digunakan dalam puisi tersebut. Data dianalisis dengan teori resistensi perempuan kulit hitam oleh Patricia Hills Collins. Teori lain adalah bahasa kiasan dan perumpamaan oleh Ruth Miller dan Robert A. Greenberg. Data tersebut dihasilkan dari kata, frase dan kalimat yang berkaitan dengan feminisme kulit hitam sebagai perjuangan perempuan kulit hitam melawan penindasan dan standar kecantikan yang terkandung dalam puisi. Cara pertama untuk melawan adalah Definisi Diri, Harga Diri, Kemandirian, dan Pemberdayaan Pribadi yang disebutkan oleh Collins. Kemudian dalam puisi menggunakan bahasa kiasan seperti metafora, simile dan personifikasi. Perumpamaan juga mencakup visual, taktil, dan aural. Akhirnya kesimpulan yang dapat ditarik adalah temuan di atas membuktikan bahwa puisi Audre Lorde dan Lucille Clifton adalah perjuangan perempuan kulit hitam melawan ketidakadilan.Kata kunci: Perempuan kulit hitam, feminisme kulit hitam, pengendalian visual, penghargaan diri yang positif, puisi.